Effect of nωnla, an inhibitor of No-synthase, on the release of tissue-plasminogem activator from rat aorta - Fracasso, J. F. [UNESP]; Silva, R. F P [UNESP]; Lepera, E. Z P [UNESP] (My University, 2003)
Alterations in the synthesis or enhanced inactivation of nitric oxide (NO) and increase in fibrin deposition in the vascular bed lead to an imbalance that can induced intravascular coagulation. NO is produced through L-arginine pathway by constitutive and inducible nitric oxide synthase (NOS). The inducible isoform can be activated by cytokines such as tumor necrosis factor alfa. We evaluated NO-induced tissue-plasminogen activator (t-PA) release from isolated aortic segments of Wistar rats measuring the fibrinolytic activity in the fibrin plate. Inhibition of NO biossynthesis with Nω-nitro-L-arginine (NωNLA) significantly attenuated the fibrinolytic activity (FA) evoked by aortic segments of this group (GII) compared to the saline group (GI). The administration of L-arginine produced restoration of FA in this group (GIII) treated with NωNLA suggesting that t-PA arising from segments of rat aorta is influenced by NO.
Keywords: Endotoxin; Nω-nitro-L-arginine; Nitric oxide; NO-synthase; Tissue-plasminogen activator; arginine; endotoxin; fibrin; n(g) nitroarginine; nitric oxide; nitric oxide synthase; nitric oxide synthase inhibitor; tissue plasminogen activator; tumor necrosis factor alpha; animal experiment; animal tissue; aorta; controlled study; disseminated intravascular clotting; drug mechanism; endothelium injury; enzyme activity; enzyme release; fibrinolysis; male; nonhuman; rat